Soy Protein-Based Emulsions: Application as Lipid Substitutes in Surimi Gels - Fali Zhang; Jian Shi; Yanfei Chen; Yao Yue; Wenzheng Shi; Tanye Xu; Min Qu (Foods)
By analyzing interfacial dynamics between soybean oil concentrations and soy protein isolate (SPI), this study established their impact on Pickering emulsion stability. Two optimal soy protein-based emulsions (EM60 with 60% oil phase; EM75 with 75%) were identified as lipid substitutes in silver carp surimi products. The results revealed that uniformly spherical droplets in EM60 enhanced interparticle interactions at emulsion interfaces. Compared to EM75 addition, EM60’s finely dispersed droplets improved gel network compactness in the surimi matrix. This increased water-holding capacity (WHC) by 12.037% and gel strength by 2414.168 g·mm. EM75 addition significantly enhanced gel whiteness by 0.8483 units (p < 0.05). It also demonstrated superior physical filling effects in sol state, reinforcing structural rigidity. As unsaturated lipids, soybean oil substitution for saturated fats (e.g., lard) contributes positively to human health. Pre-emulsified soybean oil yielded stronger structural rigidity in surimi sol than direct oil addition. Post-gelation, significant increases were observed in gel strength (+828.100 g·mm), WHC (+6.093%), and elasticity (+0.07 units). Collectively, SPI-based emulsions offer novel insights for healthy lipid substitution in surimi gels. They elucidate differential impact mechanisms on texture, WHC, whiteness, and microstructure. This provides theoretical guidance for developing premium healthy surimi products.